The Combination of Papaya Seed Juice (Carica papaya L) and Turmeric Juice (Curcuma domestica val) to Reduce Total Cholesterol Levels in Hypercholesterolemic Rat - Alldi Wahid Noor Kusuma; Ika Setyawati (Universitas Muhammadiyah Yogyakarta, 2021)
The cholesterol is found naturally in the blood. Most of it is produced in the liver. Cholesterol is very important for maintaining health and can be a problem if blood levels are too high. High serum cholesterol levels in the blood cause atherosclerosis, which in turn results in cardiovascular disorders. This study aims to determine the effect of giving a combination of papaya seed juice and turmeric to reduce total cholesterol in hypercholesterolemic rats. This is an experimental study with a pretest posttest control group design. The research subjects were 25 white rats, consisting of five groups, namely group 1 (negative control), group 2 (standar), group 3 (papaya seed juice 100 mg/kgBW/day and turmeric juice 70 mg/kgBW/day), group 4 (papaya seed juice 200 mg/kgBW/day and turmeric juice 70 mg/kgBW/day), group 5 (papaya seed juice 400 mg/kgBW/day and turmeric juice 70 mg/kgBW/ day). The treatment was given for 21 days in each group. Measurement of total cholesterol levels using the colorimetric enzymatic GPO method. Research results: the results obtained based on the paired samples T-test conducted in each group before and after treatment that group 2 has P> 0.05 and the test group 1, 3, 4, and 5 have p <0.05 so that it can be concluded that the combination of papaya seed juice and turmeric juice can reduce total cholesterol levels in hypercholesterolemic rats.